Analisis Rawan Kebakaran Hutan Di Seram Maluku Berbasis Citra Landsat 8 Menggunakan Metode Inverse Distance Weighted - Prisilia Talakua; Eko Sediyono; Sri Yulianto Joko P (Maranatha University Press, 2018)
Fire is one of the problems that must be observed by everyone around the world, because fire is a disaster that can make the occurrence of damage, changes in the earth's surface and death, to be able to see changes in the earth's surface on a burning field can be analyzed using remote-based sensing vegetation index. The purpose of this study was to analyze the value of the six types of vegetation index and with the use of IDW analysis method in the area of fire that may result from the low level of vegetation index in Seram Island, Central Maluku to know whether the analyzed areas are which is prone to fire. Data collection obtained from BMKG (data of fire point number 2015), electronic news, USGS web (landsat image 8). IDW analysis results for the NBR index, resulting in a value that shows that all areas have the potential to fire with the value generated from 0.5 - 0.6 which is a medium - high fire rate value according to the classification of values and found in the 6 districts studied.